The black swan : the impact of the highly improbable - Taleb, Nassim Nicholas, 1960- (Random House Trade Paperbacks, 2010)
Examines the role of the unexpected, discussing why improbable events are not anticipated or understood properly, and how humans rationalize the black swan phenomenon to make it appear less random.